Impact of Everolimus and Low‐Dose Cyclosporin on Cytomegalovirus Replication and Disease in Pediatric Renal Transplantation. Issue 3 (3rd February 2016) - Höcker, B.; Zencke, S.; Pape, L.; Krupka, K.; Köster, L.; Fichtner, A.; Dello Strologo, L.; Guzzo, I.; Topaloglu, R.; Kranz, B.; König, J.; Bald, M.; et al.
Abstract : In order to investigate the hypothesis that the mammalian target of rapamycin inhibitor everolimus (EVR) shows anticytomegalovirus (CMV) activity in pediatric patients, we analyzed the impact of EVR‐based immunosuppressive therapy on CMV replication and disease in a large cohort (n = 301) of pediatric kidney allograft recipients. The EVR cohort (n = 59), who also received low‐dose cyclosporin, was compared with a control cohort (n = 242), who was administered standard‐dose cyclosporin or tacrolimus and an antimetabolite, mostly mycophenolate mofetil (91.7%). Multivariate analysis revealed an 83% lower risk of CMV replication in the EVR cohort than in the control cohort (p = 0.005). In CMV high‐risk (donor+/recipient−) patients (n = 88), the EVR‐based regimen was associated with a significantly lower rate of CMV disease (0% vs. 14.3%, p = 0.046) than the standard regimen. In patients who had received chemoprophylaxis with (val‐)ganciclovir (n = 63), the CMV‐free survival rates at 1 year and 3 years posttransplant (100%) were significantly (p = 0.015) higher in the EVR cohort (n = 15) than in the control cohort (n = 48; 1 year, 75.0%; 3 years, 63.3%). Our data suggest that in pediatric patients at high risk of CMV, an EVR‐based immunosuppressive regimen is associated with a lower risk of CMV disease than a standard‐dose calcineurin inhibitor–based regimen. Abstract : This study in 301 pediatric kidney transplant recipients of the Cooperative European Paediatric Renal Transplant Initiative Registry associates the use of everolimus and low‐dose cyclosporine with a lower incidence of cytomegalovirus infection compared to a standard‐dose calcineurin inhibitor‐based regimen in patients at high risk of cytomegalovirus infection.